Som förvandlande passage: En erfarenhetsmetafysisk analys av den äldre Hans Ruins mystika poesibegrepp - Nielsen Jerneck,Hedvig Kristina Maria (2024)
In this thesis, titled "som förvandlande passage", "as transforming passage", I investigate the Finland-Swedish aesthetician Hans Ruin ́s concept of poetry as "poesiens mystik", "the mysticism of poetry". The essential aim of the thesis is both to reach a deeper analysis and understanding of Ruin ́s concept of poetry and, through this and through adding the passage as an idea and an understanding to accomplish a development of the Danish Professor of History of ideas, Dorthe Jørgensen’s methodology "erfaringsmetafysik", “metaphysics of experience”. The thesis is based on a three-folded theory – the theory of Beautiful Thinking, the theory of reading-response and the theory of passage. Together with a biographic context of Ruin, I am trying to reach an intellectual context, where I present the aesthetic influences he got from the Finland-Swedish aesthetician Yrjö Hirn, the intuitive influences he got from the Swedish philosopher Hans Larsson as well as the poetic- mystical influences he got from the French literary scholar and Jesuit Henri Brémond. In my analysis of Ruin’s concept of poetry, I present his comparison between mysticism and poetry, his idea of the mysticism of poetry as a collecting moment, and his understanding of Catharsis as the transforming and transplanting motion of poetry. In a last analyzing chapter, and through a meta-narrative of the passage, I finally present my methodological development of a direction into a relation between aesthetics, phenomenology and theology. My conclusion of this thesis is that both the concept of poetry for Ruin and my added methodological development of the metaphysics of experience, is a transforming passage. The passage in this thesis is a recurring theme since the passage is both a methodological key, a result of the development of the method, a methodological starting point of the analysis and a conclusion of Ruin ́s understanding of poetry. Thus, this thesis is my contribution to how my reading of Ruin ́s concept of poetry, through my reading of Jørgensen’s metaphysics of experience, develops an aesthetic-theological methodology in the direction of a transcendental immanence.
Keywords: poesi; mystik erfarenhet; erfarenhetsmetafysik; passage; förvandlande passage; intuition; estetik; Katharsis; systematisk teologi; estetisk-teologisk; den skønne tænkning; Hans Ruin; Dorthe Jørgensen; Walter Benjamin; Yrjö Hirn; Hans Larsson; Henri Brémond